Functional characterization of drug responses in induced pluripotent stem cell-derived cardiomyocytes from a short QT syndrome type 5 patient. (24th May 2021) - Lee, J; Hohn, A; Emmenegger, V; Ulusan, H; Akin, I; Saguner, AM; Zhou, X; Duru, F; Hierlemann, A; El-Battrawy, I
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): ETH Zurich Personalized Health and Related Technologies; German Centre for Cardiovascular Research Introduction: Short QT syndrome (SQTS) and Brugada syndrome (BrS) are rare channelopathies causing sudden cardiac death (SCD). There are only few investigations of effective therapies of SQTS and BrS linked to CACNB2 variants. Since treatment data of SQTS are sparse, we studied drug responses of induced pluripotent stem cell-derived cardiomyocyte (iPSC-CM) 2D cultures carrying a mutation in the CACNB2 gene from a SQTS type 5 (SQT5) patient with an established phenotype. We used high-density microelectrode arrays (HD-MEAs), patch clamp, and calcium-transient imaging. Purpose: To investigate the electrophysiological responses of SQT5 patient-derived iPSC-CMs upon exposure to antiarrhythmic drugs. Methods: Human iPSCs, derived from a SQT5 patient and a healthy donor, were cultured and differentiated into cardiomyocytes by temporal modulation of the Wnt signaling. For electrophysiological measurements, spontaneously beating cardiomyocytes at day 40-60 were dissociated and plated a) on petri dishes for patch clamp and calcium-transient measurements and b) directly on HD-MEAs. Antiarrhythmic drugs, including sotalol, quinidine, and flecainide, were dosed to the cells after plating as soon as stable activity levels were measured. After baseline measurements, drug doses were sequentially increased from low to high concentrations. Results: We observed spontaneous and synchronous beating of SQT5 patient- and healthy donor-derived iPSC-CMs. Quinidine, which is known to be effective for treatment of SQTS with possible differences for subtypes, prolonged field-potential duration (FPD) and action-potential duration in SQT5 patient-derived iPSC-CMs. Sotalol slightly increased FPD at 30µM as measured with HD-MEAs, whereas action-potential duration (APD) measured through patch clamp did not exhibit a notable effect at 30 µM. APD became shorter at higher concentrations, which is in line with clinical data of SQTS patients. HD-MEA measurements showed that flecainide shortened the FPD of SQT5 patient-derived CMs at 20µM. For healthy donor-derived iPSC-CMs, quinidine, sotalol, and flecainide prolonged FPDs in HD-MEA measurements. Using calcium-transient imaging, quinidine showed a slight antiarrhythmic effect, whereas sotalol did not have antiarrhythmic effects. Conclusion: We used HD-MEAs, patch clamp, and calcium-transient imaging to analyze electrophysiological responses of SQT5 patient-derived iPSC-CMs upon dosage of antiarrhythmic drugs. Our preliminary results show that quinidine - but not flecainide - could prolong the repolarization duration in SQT5 patient-derived iPSC-CMs.